STUDENTS' HABITS OF MIND IN BIOLOGY LEARNING AS A REPRESENTATION DEEP LEARNING PREPARATION - Dina Alfiyana; Muhammad Syaipul Hayat; Praptining Rahayu (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2026)
This study aims to determine students' readiness and thinking habits in deep learning-based biology instruction, based on this premise. This research was conducted using descriptive qualitative and quantitative methods, in which data were collected through questionnaires and observations during the learning process, with interviews to support students' opinions. This study involved 103 students from grade X digital media at SMA Islam Sultan Agung 1 Semarang, who were studying biology material on environmental change. The research collected through the questionnaire showed that the self-regulation score was 82 (good), the critical thinking score was 80 (good), while the creative thinking score was 68.50 (enough). The observation results showed that the self-regulation score was 80.56 (good), the critical thinking score was 62.50 (enough), and the creative thinking score was 69.44 (enough). Interview data corroborate that self-regulation is optimal, but critical and creative thinking have not become a habit in students' thinking. Therefore, the thinking habits of class X students at SMA Islam Sultan Agung 1 Semarang still need improvement, especially in creativity and critical thinking.